2021
DOI: 10.1159/000519838
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Early Gastric Cancer after <b><i>Helicobacter pylori</i></b> Eradication

Abstract: <b><i>Background:</i></b> Based on evidence that <i>Helicobacter pylori</i> eradication reduces the development of gastric cancer and other diseases such as peptic ulcer, eradication therapy has prevailed. However, gastric cancer can develop even after successful eradication. <b><i>Summary:</i></b> In this review article, we searched for studies that identified the characteristics of primary and metachronous gastric cancers after <i>H. pylori<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…However, successful eradication does not completely prevent gastric cancer occurrence, and the clarification of related risk factors in eradicated cases is clinically important for examiners using EGD. In previous investigations, several factors, such as an older age, smoking history, long-term usage of a PPI, and more severe GMA, have been demonstrated to be related to occurrence of gastric cancer (8)(9)(10). The results of the present study of H. pylori-eradicated patients who underwent EGD as part of an annual checkup showed that a smoking history and anti-secretory usage were not significant risk factors, whereas an older age at the time of H. pylori eradication and higher degree of GMA were demonstrated to be significant risk factors for gastric cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, successful eradication does not completely prevent gastric cancer occurrence, and the clarification of related risk factors in eradicated cases is clinically important for examiners using EGD. In previous investigations, several factors, such as an older age, smoking history, long-term usage of a PPI, and more severe GMA, have been demonstrated to be related to occurrence of gastric cancer (8)(9)(10). The results of the present study of H. pylori-eradicated patients who underwent EGD as part of an annual checkup showed that a smoking history and anti-secretory usage were not significant risk factors, whereas an older age at the time of H. pylori eradication and higher degree of GMA were demonstrated to be significant risk factors for gastric cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The development of gastric cancer after successful eradication has been reported to be influenced by several factors, such as the age, time since eradication, smoking history, proton pump inhibitor (PPI) usage, and degree of gastric mucosal atrophy (GMA) (4)(5)(6)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Shichijo et al. ( 51 ) showed that timely eradication of H. pylori also increased the risk of developing gastric cancer. Therefore, timely and effective detection and management of high-risk groups, as well as 2nd-look endoscopy, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent development and widespread use of IEE and magnifying endoscopy have improved the endoscopic diagnosis of gastric cancer [ 23 ]. IEE is useful for diagnosing gastric cancer after eradication, which is usually difficult to detect [ 63 ]. In a recent study, we showed that photodynamic endoscopic diagnosis—based on the fluorescence of photosensitizers that accumulate in tumors—may be useful in the diagnosis of early gastric cancer regardless of the endoscopist’s experience and is useful for tumor detection; however, its usefulness has not been established because no prospective studies evaluating its usefulness have been performed [ 64 ].…”
Section: Gastric Cancer Screening Methods Used In Japanmentioning
confidence: 99%